2012
DOI: 10.1302/0301-620x.94b9.28130
|View full text |Cite
|
Sign up to set email alerts
|

The operative management of osteoporotic fractures of the knee

Abstract: This review considers the surgical treatment of displaced fractures involving the knee in elderly, osteoporotic patients. The goals of treatment include pain control, early mobilisation, avoidance of complications and minimising the need for further surgery. Open reduction and internal fixation (ORIF) frequently results in loss of reduction, which can result in post-traumatic arthritis and the occasional conversion to total knee replacement (TKR). TKR after failed internal fixation is challenging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 65 publications
4
67
0
2
Order By: Relevance
“…Insgesamt können wir die Aussagen der Literatur bestätigen, dass die Frakturendoprothetik beim geriatrischen Krankengut bei definierten Indikationen mit einem besseren funktionellen Outcome und vergleichbarer oder sogar geringerer Komplikationsrate einhergeht [4].…”
Section: Medizinische Aspekteunclassified
“…Insgesamt können wir die Aussagen der Literatur bestätigen, dass die Frakturendoprothetik beim geriatrischen Krankengut bei definierten Indikationen mit einem besseren funktionellen Outcome und vergleichbarer oder sogar geringerer Komplikationsrate einhergeht [4].…”
Section: Medizinische Aspekteunclassified
“…Malviya et al 15 recommended stemmed cemented components because they are thought to confer primary stability, allowing early, unrestricted mobilization. Many other authors share this opinion, although Bohm et al 24 suggested that the surgeon might forgo the use of a stemmed tibial implant in the presence of good circumferential cortical support. Although most of the literature supports the use of cement, its effect on associated fracture union remains largely unknown ( Figure 1).…”
Section: Acute Primary Total Knee Arthroplastymentioning
confidence: 99%
“…In Schatzker types I, II, and IV, the authors suggested using intramedullary fi xation, supplemented by internal fi xation if the fragments are large enough. Finally Schatzker type V and VI involving both condyles, with or without metaphyseal extension, are the most demanding to manage, and the authors suggested a combination of tibial stems and plate fi xation [ 4 ].…”
Section: Surgical Techniquementioning
confidence: 99%
“…Some authors described an unacceptable failure rate (79 %) and unsatisfactory results for ORIF in elderly patients [ 1 ]. For these reasons there is still a concern about treating tibial plateau fractures in elderly patients using ORIF [ 4 ].…”
Section: Introductionmentioning
confidence: 99%